MENGURAI BEBAN PAJAK MELALUI PENGARUH RASIO PROFITABILITAS DAN STRUKTUR MODAL PADA EMITEN HOTEL DI BEI - Herawati Khotmi; Dewi Rispawati (Jurnal Aplikasi Perpajakan, 2026)
This study aims to examine the partial effects of profitability and capital structure on tax expenses in hotel companies listed on the Indonesia Stock Exchange (IDX). Profitability is measured using Return on Assets and Return on Equity, whilst capital structure is measured using the Debt to Equity Ratio. This is a quantitative study utilising SPSS statistical software. The research sample comprises eight hotel companies listed on the Indonesia Stock Exchange (IDX). The observation period spans five years. The data analysis technique employed is multiple regression analysis. The analysis was conducted using classical assumption tests, the R-squared test, and hypothesis testing. The results of the study indicate that Return on Assets has a positive effect on tax expense, Return on Equity has a positive effect on tax expense, and the Debt to Equity Ratio has a positive effect on tax expense. It is recommended that future research expand the variables by adding moderating or mediating factors, such as Good Corporate Governance, company size, or tax incentive policies, and broaden the research sample to include, for example, manufacturing companies.